When any number raised to the power of zero is equal to 1, we can simplify the expression as follows:
−4^0 x^2 y^0 z^5 = −1 * 1 * 1 * z^5 = -z^5
Therefore, the simplified expression is -z^5.
Apply the Power of Zero Rule of Exponents to simplify −4^0 x^2 y^0 z^5.(1 point)
3 answers
wrong
I apologize for the mistake. Let's simplify the expression following the Power of Zero Rule of Exponents:
−4^0 x^2 y^0 z^5 = -1 * 1 * 1 * z^5 = -z^5
Therefore, the simplified expression is -z^5.
−4^0 x^2 y^0 z^5 = -1 * 1 * 1 * z^5 = -z^5
Therefore, the simplified expression is -z^5.